Multicomponent Reactions Catalyzed by Lanthanides - Tambade, Pawan J.; Patil, Yogesh P.; Bhanage, Bhalchandra M. (Current Organic Chemistry, 2009)
This review covers some important developments in the field of multicomponent reactions catalyzed by lanthanides. Various aspects of well known multicomponent reactions such as Biginelli, Hantzsch synthesis, Ugi reaction, Mannich reaction, Povarov reaction, Kabachnik-Fields reaction and other reactions catalyzed by various lanthanides, role of catalyst, its recyclability, and reaction conditions were discussed in detail.